Adding Risks: Some General Results about Time Diversification - Kin Lam; Liang Zou (Tinbergen Institute, 2000)
We show in general that risky investments become more attractive asthe investment horizon (n) lengthens.Specifically, any investor's maximal expected utility directlyincreases with n, as well as the investor's willingness toallocate more capital to the risky assets if his optimal strategy isbounded by the leverage constraint.
Keywords: G11; 330; Time diversification; expected utility; long-term capital allocation; Betriebliche Investitionstheorie; Investitionsrisiko; Zeit; Theorie